Gender Analysis of Crop and Animal Husbandry Practices in Hill Agriculture - Ashish Singh , N. V. Kumbhare , Premlata Singh , Nishi Sharma , Neelam Patel; Bishal Gurung (Indian Journal of Extension Education, 2016)
Women farmers have been the vital workforce in agriculture, as they manage agricultural activities along with the household chores. The study was conducted in purposively selected Almora and Nainital districts of Uttarakhand, India. The two blocks each from Almora (Takula and Hawalbagh) and Nainital (Betalghat and Dhari) were selected randomly. Further, two villages from each block were selected randomly. Fifteen women and five men farmers from each village were selected through simple random sampling. Thus, a total of 120 women and 40 men respondents from two districts constituted the sample for the study. The study revealed gender gap in crop husbandry, animal husbandry and daily routine practices in hill agriculture. The gender analysis in crop husbandry practices revealed that a majority of the women farmers were engaged in weeding (94.60%) followed by thinning and gap filling (87.82%), storage (82.23%), threshing and winnowing (74.77%), irrigation (70.52%), loading and unloading (63.58%) were the major activities done by women farmers. Agricultural activities like sowing (66.46 %), seed treatment (51.42%) and harvesting (52.33%) were done by women farmers with a significant help from men farmers. The activities like fodder cutting (88.27%) and cleaning animal shed (86.75%) were the activities demand larger time share of women farmers. Other activities like feed and fodder to the animals (70.47%), milking (75.67%) and animal care (77.50%) were also majorly done by women. Most of the activities like food preparation (99.00%) followed by collection of fuel and fodder (97.00%), collecting water (89.40%) and family care (88.20%) were the major time consuming activities done by the women farmers as compared to their male counterpart.